THE TELEPHONE INTERVENTION MEASURE - Duartes D., Edwin (2017)
The article contains a doctrinal, jurisprudential and legal analysis of the subject of telephone interventions in crimes of serious gravity, whose purpose is to clarify these crimes. This intervention must be ordered  and  controlled by a judge, protected by a reasoned resolution. The legal context revolves around what exists in Costa Rica in this area, invoking, in some cases, comparative jurisprudence. The paper offers a documented version of the intervention techniques, the existing legal limitations in relation to their scope and, what are the effective spheres of this figure and what their probative value in the current procedural system